Bulk serum extracellular vesicles from stressed mice show a distinct proteome and induce behavioral and molecular changes in naive mice - Monteleone, Melisa Carolina (2024)
Chronic stress can trigger several pathologies including mood disorders for which no clear diagnostic molecular markers have been established yet. Attractive biomarker sources are extracellular vesicles (EVs). Evs are released by cells in health and disease and contain genetic material, proteins and lipids characteristic of the cell state. Here we show that Evs recovered from the blood of animals exposed to a repeated interrupted stress protocol (RIS) have a different protein profile compared to those obtained from control animals. Proteomic analysis indicated that proteins differentially present in bulk serum Evs from stressed animals were implicated in metabolic and inflammatory pathways and several of them were previously related to psychiatric disorders. Interestingly, these serum Evs carry brain-enriched proteins including the stress-responsive neuronal protein M6a. Then, we used an in-utero electroporation strategy to selectively overexpress M6a-GFP in brain neurons and found that M6a-GFP could also be detected in bulk serum Evs suggesting a neuronal origin. Finally, to determine if these Evs could have functional consequences, we administered Evs from control and RIS animals intranasally to naïve mice. Animals receiving stress EVs showed changes in behavior and brain M6a levels similar to those observed in physically stressed animals. Such changes could therefore be attributed, or at least in part, to EV protein transfer. Altogether these findings show that EVs may participate in stress signaling and propose proteins carried by EVs as a valuable source of biomarkers for stress-induced diseases.